Impact of Climate Change on the Design Parameters of Heating, Ventilation and Air Conditioning Systems for Manned Spacecraft - Adeyemi, K. O.; Ozigis, I. I.; Zarmai, M. T.; Ishola, S. I. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
Climatic design information has been published for several locations in the world by American Society of Heating, Refrigerating and Air-Conditioning Engineers (ASHRAE) but there has not been data for Nigerian cities in these publications. Therefore, this study was embarked upon to bridge the gap in knowledge. The study of impact of climate change on the design parameters of Heating, Ventilation and Air Conditioning (HVAC) systems for spacecraft cabin environment is presented with particular focus on Ikeja-Lagos, Nigeria. Firstly, the characteristics climate parameters such as outdoor dry-bulb temperature, coincident wet-bulb temperature, relative humidity, pressures, air composition, among others as it affects manned spacecraft were discussed. The data for climatic parameters for Ikeja-Lagos, Nigeria, for a period of fifteen years (1995-2009) were obtained from Nigerian Meteorological Agency (NIMET), Oshodi-Lagos. Statistical data and Microsoft excel were used for evaluation of variation trends of the climate parameters for departure city. This is very important in determining thermal human comfort in spacecrafts on ascent. Results obtained from this study are hereby presented. The Ikeja-Lagos dry-bulb temperature average results obtained were 33.81°C, 32.98°C, 32.3°C, 22.1°C, 21.19°C, 20.43°C, 23.84°C and 31.65oC.at 0.4%, 1.0%, 2.0%, 97.5%, 99.0%, 99.6%, median of extreme lows and median of extreme highs, respectively. The Ikeja-Lagos relative humidity average results were 116.3, 112.65, 109.14, 99.83 and 49.42 at 0.4%, 1% and 2.0% occurrence as well as at median of extreme highs and median of extreme lows, respectively. Ikeja-Lagos had mean coincident dry bulb temperature of 33.81°C and 32.98°C at 0.4% and 1% percentile respectively. The dry bulb temperature for Ikeja-Lagos was determined to be an average range from 20.43°C to 22.1°C between January to December, in the period of 1995-2009, at 97.5% 99% and 99.6% percentile respectively. These results provide values of design parameters which are useful in the design of HVAC for space crafts with climate change adequately taken into consideration as it applies to Ikeja-Lagos, Nigeria